2013
DOI: 10.1111/bij.12065
|View full text |Cite
|
Sign up to set email alerts
|

Musin Morocco: a Quaternary sequence of intraspecific evolution

Abstract: North Africa is an intricate biogeographical region at the crossroads of immigration waves from tropical Africa and Asia. Species confined between various barriers (Atlas Mountains, arid environments such as the Sahara in the south, water masses such as the Mediterranean Sea in the north, and the Atlantic Ocean in the west) were generally forced to adapt locally to environmental changes instead of tracking their habitat by shifting their distribution area. The present study aims at providing first insight into… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 90 publications
2
14
0
Order By: Relevance
“…This suggests that, for M. arvalis at least, body size reduction between fossil and modern specimens has not been a response to long‐term, natural global warming since the LGM (Millien et al ), but rather a more recent anthropogenic phenomenon (Sheridan and Bickford ). A similar trend observed in mice species has been linked with pervasive anthropogenic perturbations—from habitat destruction to climate change (Cassaing et al ; Stoetzel et al )—during very recent times. However, the archaeological record for Mainland Orkney shows size reduction in voles much earlier, between the 4th and 12th centuries AD, suggesting that anthropogenic impacts could have had greater/earlier effects on small mammals in confined/insular environments and/or in higher latitudinal locations.…”
Section: Discussionsupporting
confidence: 70%
“…This suggests that, for M. arvalis at least, body size reduction between fossil and modern specimens has not been a response to long‐term, natural global warming since the LGM (Millien et al ), but rather a more recent anthropogenic phenomenon (Sheridan and Bickford ). A similar trend observed in mice species has been linked with pervasive anthropogenic perturbations—from habitat destruction to climate change (Cassaing et al ; Stoetzel et al )—during very recent times. However, the archaeological record for Mainland Orkney shows size reduction in voles much earlier, between the 4th and 12th centuries AD, suggesting that anthropogenic impacts could have had greater/earlier effects on small mammals in confined/insular environments and/or in higher latitudinal locations.…”
Section: Discussionsupporting
confidence: 70%
“…Rohlf and Marcus 1993;Bookstein 1991;Mitteroecker and Gunz 2009). Such methods, based on landmarks or outline analyses, have been used to tackle many topics regarding rodent evolution: evolutionary patterns along fossil lineages (Renaud et al 1996Piras et al 2009;Stoetzel et al 2013), diversification among species, addressing the respective role of adaptation and neutral evolution (e.g. Cardini 2003;Monteiro et al 2005;Macholan 2006;Michaux et al 2007a); differentiation between populations, investigating the role of environmental variations (Renaud 1999;Fadda and Corti 2001;Michaux 2003, 2007;McGuire 2010;Helvaci et al 2012), processes favoring co--occurrence among species , patterns and route of colonization (Valenzuela--Lamas et al 2011;Siahsarvie et al 2012;Cucchi et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…The impact of human activities and inter-specific competition were likely involved (other murid species arriving in Morocco during Holocene, especially the house mouse around 3000 BP) and seem to have had a stronger influence than climatic changes on the morphological evolution of Mus. It is interesting to note here that despite a clear morphological stability throughout the El Harhoura 2 stratigraphy (no statistical difference between the 8 studied levels), Stoetzel et al (2013) demonstrated a significant relationship between tooth shape (m1 and M1 first DFA axis) and the diversity indices (Shannon and Simpson). This may reflect changes in morphology related to biotic or abiotic environmental changes (e.g.…”
Section: Palaeoecological Resultsmentioning
confidence: 61%
“…In order to classify the archaeological specimens, Discriminant Analyses were performed using modern species found in Morocco today as a reference sample, and a posteriori specific assignations for fossil specimens were performed (Baylac and Friess, 2005;Evin et al, 2013;Stoetzel et al, 2013). Size (logarithm of the centroid size), playing an important role to discriminate white-toothed shrews was included in the analyses in order to optimize the specific classification (Cornette et al, 2015a).…”
Section: Morphometrics Analysesmentioning
confidence: 99%
See 1 more Smart Citation